Inversed Matrixes in Electric Circuits Parameters Estimation by Oriented Graphs - Pavlikova, Sona; Maga, Dusan; Simak, Boris (Communications - Scientific letters of the University of Zilina, 2013)
The base of electric circuit analysis is often set up on numerical methods. When taking a look into the principle of any numerical method, a matrix calculus always rises out. The larger the problem is, the larger is the size of the matrix, representing the logical structure of the solved problem [1]. The problem (especially from the mathematical point of view) is in acquiring the inverse matrix, which can be solved with some of a large scale of available numerical (or analytical; based on the size of matrixes) methods. This paper shows another possible approach to obtaining the inverse matrix. The graph theory has already been successfully used to invert the matrixes; although, the idea of evaluating the alternating paths, presented by authors, is completely new and had not been used before. The utilization of the designed procedure is demonstrated on a part of an analogue signal processing filter. This technology gives a new tool to software designers and could speed up the numerical solutions; or, in case of impossible analytical and/or diverge numerical technique can lead to a successful and reasonable solution.